First experience of using favipiravir in the first healthcare worker patient with moderate case of Coronavirus Disease 2019 (COVID-19) at Sulianti Saroso Infectious Disease Hospital, Jakarta, Indonesia: a case report - Pompini Agustina Sitompul; Nina Mariana; Adria Rusli (Sekretariat Badan Penelitian dan Pengembangan Kesehatan, 2021)
Background: During the early period of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic, there was no approved and definitive drug available for the treatment of COVID-19. Favipiravir, chloroquine, hydroxychloroquine was used for re-purposing drugs while their efficacy and safety remained a major concern for healthcare workers. Clinical trial to assess efficacy and safety were ongoing. Case presentation: We present here the case of a 38-year-old woman, the first case of a healthcare worker diagnosed with COVID-19 who had moderate type, including first experience treatment with favipiravir in Sulianti Saroso Infectious Disease Hospital, Jakarta, Indonesia. We present the clinical characteristics, chest X-ray, clinical laboratory profiles, the treatment process with favipiravir and hydroxychloroquine as well as the clinical outcome of moderate type COVID-19 patient. Conclusion: This case highlights that considering the use of emergency intervention outside of clinical trial in the COVID-19 population, the informed patient consent has been given and the use of emergency intervention was monitored. Keywords: COVID-19, favipiravir, medical worker, case report, Jakarta Abstrak Latar belakang: Periode awal pandemi Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), belum terdapat obat yang disetujui dan pasti tersedia untuk pengobatan COVID-19. Favipiravir, chloroquine, hydroxychloroquine digunakan sebagai obat dengan indikasi baru yang sementara efektifitas dan keamanannya menjadi perhatian para petugas medis. Penyajian kasus: Disini kami melaporkan kasus wanita umur 38 tahun, merupakan kasus pertama seorang tenaga kesehatan Rumah Sakit terdiagnosis Coronavirus Disease 2019 (COVID-19) dengan penggunaan terapi favipiravir untuk pertama kalinya di Rumah Sakit Pusat Infeksi Sulianti Saroso, Jakarta, Indonesia. Berikut ini kami gambarkan karakteristik klinis, hasil foto thorak, profil laboratorium dan proses terapi menggunakan favipiravir and hidroxychloroquine serta hasil akhir pada kasus COVID-19 derajat sedang. Kesimpulan: Kasus ini menggaribawahi bahwa pertimbangan penggunaan kegawatdaruratan obat antivirus diluar uji klinis pada populasi pasien COVID-19, pasien telah memberikan persetujuan dan penggunaan obat-obat tersebut dimonitor. Kata kunci: Covid-19, favipiravir, tenaga kesehatan, laporan kasus, Jakarta